Wiley GAAP 2018 : interpretation and application of generally accepted accounting principles - Flood, Joanne M. (John Wiley & Sons, Inc., 2017)
Get the most comprehensive coverage of the FASB Codification and the latest FASB updates in a single volume Wiley GAAP 2018: Interpretation and Application of Generally Accepted Accounting Principles is a thorough study and analysis of all US Generally Accepted Accounting Principles (GAAP) set forth in the pronouncements of the FASB (Financial Accounting Standards Board) Codification. All topics are explained with relevant terminology and practice-oriented real world examples. Each chapter is composed of a discussion of perspectives and issues, definitions of terms, concepts, rules, and examples. US GAAP is constantly being updated, and its users require expert interpretation and explanation of the relevant principles. This book provides the most comprehensive coverage of each Codification topic. It contains clear, user-friendly guidance on every pronouncement.-Fully up-to-date with all the latest changes, including those to inventory, financial instruments, revenue, and leases -Includes more real-world examples and illustrations than competing titles -Arranged according to the FASB Codification, all topics are referenced to the Codification Wiley GAAP 2018 renders GAAP more understandable and accessible for research and is designed to reduce the amount of time and effort needed to solve accounting research and implementation issues, making it the best go-to source for CPAs and others working in accounting.